The impact of the Green Revolution and prospects for the future - Pinstrup-Andersen, Per; Hazell, Peter B. R. (Informa UK Limited, 1985)
This article evaluates the impact of the Green Revolution with regard to its impact on food production and production fluctuations, its direct impact on poverty and nutrition, and its indirect income and employment effects. It also considers the role of women in technological change and the environmental effects of the Green Revolution.